2015
DOI: 10.7287/peerj.preprints.1591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of mature oak stands and spruce plantations on soil-dwelling click beetles in lowland plantation forests

Abstract: Most European forests have been converted into forest plantations that are managed for timber production. The main goal of this paper was to determine the difference between mature native sessile oak (Quercus petraea) stands and non-indigenous Norway spruce (Picea abies) plantations with respect to communities of Athous click beetles in approximately 6,500 ha of lowland plantation forest area in the Czech Republic. Athous subfuscus was the most abundant and widespread species, followed by A. zebei and A. haemo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Another potential explanation might be that the current presence and extent of mature oak stands is below the threshold area and fragmentation caused by isolation that is acceptable for the successful development of populations of oak-associated click beetles (Alexander, 2002). This appears to be well reflected in the fact that only two relatively common species (Loskotová & Horák, 2016) significantly preferred oak stands, whereas four species were associated with spruce plantations. The opposite relationship was observed for diversity and, thus, we concluded that tree species that is not native in the studied area can negatively influence the diversity of the family; however, why the other traits responded differently remains unclear (Loehle, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Another potential explanation might be that the current presence and extent of mature oak stands is below the threshold area and fragmentation caused by isolation that is acceptable for the successful development of populations of oak-associated click beetles (Alexander, 2002). This appears to be well reflected in the fact that only two relatively common species (Loskotová & Horák, 2016) significantly preferred oak stands, whereas four species were associated with spruce plantations. The opposite relationship was observed for diversity and, thus, we concluded that tree species that is not native in the studied area can negatively influence the diversity of the family; however, why the other traits responded differently remains unclear (Loehle, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Oaks that were dominant in the study territory in the past (Neuhauselova & Moravec, 2001) are mostly no longer present as a dominant species (Loskotová & Horák, 2016). One potential reason why oak stands did not lead to the expected promotion of the majority of the studied taxa was that total area of broadleaved stands was relatively low and isolation was high compared with in conifer plantations (Loskotová, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albeit neotropical forests inclusion in the biological hotspots of our planet (Foley et al, 2007;Chazdon et al, 2009), the forests and the species encompassed are threatened by local and global anthropogenic stressors (Carnus et al, 2006;Loskotová and Horák, 2016). Scientist also highlight that the conservation of neotropical forest, such as the Brazilian Amazon (Amazonia) represents a core challenge for regulating earth's functioning and ultimately humankind (e.g.…”
Section: Introductionmentioning
confidence: 99%